(untitled) (Interdisciplinary Studies Journal, 2021)
This article seeks to reconstruct violence as a historical category, produced and reproduced in the order of capital, capturing its objective and subjective roots. The construction of violence, in class society, does not go through a natural process, but is produced from the social, political and economic conditions whose determinationsof capitalist society generate the material and effective basis for its perpetuation. From a literature review on the categories of structural violence, social relations and capitalism, it was possible to learn that violence is a structuring phenomenon ofcapital and therefore its overcoming is also diametrically related to overcoming the capitalist mode of production, that is, it implies the construction of a new social order, freed from the shackles of exploitation and domination of the hegemonic bourgeois pattern.